Formation of Novel Amino Vic-dioxime Complexes of Cu(II), Ni(II), Co(II) and Cd(II) of 1,3-Dioxalane Groups Containing the Oxime Moiety: Thermal, Magnetic and Spectral Studies - Duman, Sibel; Sekerci, Memet (Chem Soc Pakistan, 2012)
A novel substituted vic-dioxime ligand containing the amino group, N,N'-[2,2'-{ethane-1,2-di-yl-bis(oxy)bis(2,1-phenylene)}bis(N'-hydroxy)-2-(hydroxyimino)acetimidamide] (L-1) has been prepared from 1,2-bis(o-aminophenoxy)ethane, anti-chloroglyoxime. The new complexes derived from L-1 with Cu(II), Ni(II), Co(II) and Cd(II) complexes of 6,7-O-Cyclopentlydine-1-amino-4-azaheptane (L-2) have been reacted at 60-65 degrees C temperature. The ligand(1):metal:ligand(2) ratio of these complexes have been found to be 1:2:2. The new Cu(II), Ni(II), Co(II) and Cd(II) complexes of these ligands are proposed to be octahedral. These new complexes have been characterized by elemental analyses, molar conductivity, magnetic susceptibility, IR. H-1-NMR, UV-Vis spectra and TGA techniques.
Keywords: Vic-dioxime; Transition metal complexes; amine